ICT-based solution for efficient fecal sludge management: An experience from Bangladesh. Issue 4 (April 2023) - Jakariya, Md.; Nahla, Turasa; Ahmed, Silvia; Ishtiak, Taoseef; Islam, Md. Tahmidul; Alam, Md. Sajadul; Ali, Ahmed; Uddin Ruman, Md. Sharif; Saad, Saman; Bhattacharya, Prosun; Van der Voorn, Tom; Islam, Md. Aminul; et al.
Abstract: In Bangladesh, people primarily depend on on-site sanitation facilities (OSSF) with an immense challenge in achieving safe sanitation due to unplanned infrastructure development, improper management of fecal sludge, and inadequate monitoring. The commitment of attaining Sustainable Development Goals (SDG) 6.2 (ensuring safe sanitation for all) by 2030 requires immediate attention in the management of fecal sludge for low-middle income countries. This paper presented the findings, challenges, and possible ways forward from a study conducted to provide data for Information and Communication Technology (ICT)-based fecal sludge management (FSM) at a municipality in the northwest of Bangladesh. A total of 18, 808 households and 407 institutions in Saidpur municipality, a non-sewered town in Nilphamari district, were studied to understand the type of containment structures and on-ground desludging practices. The study showed around 10% of containments were connected to the drains illegally, 95% of the people in Saidpur practiced unsafe disposal, and 7% still practiced open defecation. To identify these malpractices, the study also implemented an ICT-based sustainable solution through a web application that enabled the local administrator to have a global look at the sanitation scenario of the municipality. The dashboard was developed to create a total sanitation monitoring system, identify defaulters, allow target-based safe managed sanitation service strategies, and ensure sustainability in FSM. The study highlighted the accessibility of vacuum truck services projecting through a spatial map and identified methods to empty the septic tanks where Vacutag services are unavailable by engaging local pit emptiers. The innovative approach of fecal sludge management will help not only to improve the existing sanitation practices but also raise community awareness to ensure sustainable sanitation system. Altogether, the web system will work as a medium to manage the faecal sludge for the existing co-compost plant where the faeces is converted into organic soil conditioner, creating prospects for a green business mechanism. Highlights: 10% of households illegally connected tanks with drains and open water bodies. 95% of the people in Saidpur practiced unsafe disposal. Despite sanitation infrastructure, around 7% of households practiced open defecation. A web application was designed to visualize the sanitation scenario of the town and promote safe sanitation. A web application of ICT-based sustainable solution for fecal sludge management aligning with SDG #6 and #9.